DETERMINATION OF PHENOLIC SUBSTANCES AND ANTIOXIDANT ACTIVITIES IN SOME GRAPE CULTIVARS BY HPLC - Ruhan lknurGazioglu Sensoy (Journal of Animal and Plant Sciences, 2012)
Every day that passes, both researchers and consumers are ever more interested to explore phenolic compounds in foods, their antioxidant activities and the impact on human health. This study was carried out to determine the phenolic substances and antioxidant activities of juices of five grapes cultivars (Silfoni, Agin Beyazi, Kis Kirmizisi, Okuzgozu and Ercis) grown in Van province of Turkey by the means of High Performance Liquid Chromatography (HPLC). While different values of phenolic substances were detected for different cultivars, the highest antioxidant activities (5.74 ± 2.38 TEAC mmol l -1) were identified in cv. Kis Kirmizisi. Gallic acid was only detected in cv. Ercis (2.78 ±0.09 mg l-1).
Keywords: Grape; Phenolic substances; Antioxidant activity